Diagnóstico y propuesta para el diseño de una campaña de comunicación social; para la educación vial en el cantón Sigsig, provincia del Azuay (periodo mayo –diciembre 2013) - Sánchez Chuva, Hector Oswaldo (2014)
In this thesis, "DIAGNOSIS AND MOTION FOR DESIGN OF SOCIAL COMMUNICATION CAMPAIGN FOR EDUCATION IN THE CANTON ROAD Sigsig , PROVINCE OF AZUAY " ( PERIOD JANUARY - DECEMBER 2013 ) clearly demonstrates the problem of education vial by passing through Canton Sígsig - Azuay province , for from this context , the main fact is established. Due to the limitations of local road education, research allowed to identify potential solutions to existing problems. Qualitative methods which is a technique that brings social reality and then make a research and methodological precision depth: During the investigative process employing such methods as necessary. It is a research method that discovers the social context and then leads to an exploration of the phenomenon with an accurate check. Through this phenomenon is a way to investigate social phenomena that have particular objectives. The qualitative method described incidents descriptively relevant and relates to the social context by using the phenomenon of study as an instance of social organization. The qualitative techniques used for data collection are participant observation, in-depth interviews and focus groups. These techniques seek to understand and explain the development of a social phenomenon. The survey is part of the methodology yielded quantitative data from a questionnaire designed applied to a portion of the population, in order to meet their analysis on the issues mentioned. From the results? Through what means of communication obtained information about driver education? In the sample indicates that 31% had received information on the radio and 23% considered not received by any means. 21% indicated receiving driver education by television , 8% said that was helped by circulating flyers and 6% of people in other cities , 5% through talks , 4% through magazines and 1 % say they have received through classes in schools and existing traffic regulations . This shows that there is an ongoing campaign to cover road safety education at various stages of life of a person. That is why society from small start learning bad attitudes driver education. We conclude that the theories that were used during this project were essential to understand why the stock Sígsig has a lack of driver education. During diagnosis were able to recognize the symptoms of the problem and diagnose its cause to support an effective solution.